Vergessene Opfer von Mord und Missbrauch: Behindertenmorde unter deutscher Besatzungsherrschaft in der Ukraine (1941-1943) und ihre juristische Aufarbeitung in der Sowjetunion - Penter, Tanja (Journal of modern European history, 2019)
In November 1943, shortly after the liberation of the occupied territories by the Red Army, three mass graves with 144 corpses were discovered in a former colony for disabled children in the Zaporizhia region. The disabled inmates had been shot in two mass murder actions by German SS and Wehrmacht units in October 1941 and in March 1943. During the course of the investigations into the case in 1944 by the People's Commissariat for Internal Affairs (NKVD), seven former Soviet employees of the colony, among them four women, were put on trial and convicted for complicity with the Germans in the crime. The trial not only condemned the murder of the disabled, but also revealed their sexual abuse under the German occupation and in Soviet pre-war times. This article combines three different research perspectives. First, the previously unknown context of the crime is described for the first time on the basis of newly accessible Soviet file material from the Ukrainian secret service archives. In the process, the differing logics behind both the locals and Germans’ roles in the events surrounding the murder are brought to light and examined in the broader context of the German occupation of the Ukraine. Second, the legal treatment of the crime by a Soviet military tribunal is viewed against the background of the general prosecution of Nazi criminals and Soviet collaborators in the Soviet Union. Third, the current handling of the crime in the local Ukrainian culture of remembrance is surveyed. This reveals in particular the consequences of the Soviet memory policies that continue to this day.
Gesehen am 14.08.2019